Sistema embarcado para determinação remota de índices de conforto térmico - Santos, Anderson Bernardo dos (2013)
The objective of this study is the development of a device for remote monitoring of the environment thermal comfort index, based on the index globe temperature and humidity (WBGT).-This system was called SISDERECT System (Remote Determination of Thermal Comfort). The developed system uses microcontroller and low-cost sensors more accurately than the methods currently used in the determination of this index. Since it is an acquisition device and a data processing machine, is it possible to collect data in a shorter time and with a larger number of samples. The system of automatic determination of thermal comfort index is connected to collector modules, comprising sensors for relative humidity and temperature. This system allows local data storage via SD memory card and data transmission via ethernet to a network server, responsible for storing and allowing access to the data collected in real time via the Internet, also allowing to produce reports from the data collected. The system was developed using an Arduino prototyping board and peripheral modules connected via expansion cards, known as Shields. The data collected by SISDERECT was compared with traditional determination methods, using the WBGT gauge and semiautomatic methods, using datalogger through HOBOS datalogger. The SISDERECT System now allows the thermal comfort of an environment to be studied remotely and data is stored in a database for later reporting. Statistical analysis demonstrated the feasibility of using SISDERECT for determining the thermal comfort index, as compared to methods used for the determination of this index.